Progress in Fertility Preservation Strategies in Turner Syndrome - Ye, Mudan; Yeh, John; Kosteria, Ioanna; Li, Li (Frontiers in Medicine, 2020)
Growth retardation and gonadal dysgenesis are two of the most important clinical manifestations of Turner syndrome (TS). As premature ovarian failure generally occurs early in life in women with TS, these patients should be counseled and evaluated as early as possible for discussion of optimal and individualized fertility preservation strategies. Infertility seriously affects the quality of life of women with TS. For those who have ovarian reserve, the theoretical options for future fertility in TS patients include cryopreservation of oocytes, ovarian tissues, and embryos. For those who have already lost their ovarian reserve, oocyte or embryo donation, gestational surrogacy, and adoption are strategies that allow fulfillment of desire for parenting. This review describes the etiologies of infertility and reviews the fertility preservation strategies for women with TS.